2019
DOI: 10.1039/c9nr04768a
|View full text |Cite|
|
Sign up to set email alerts
|

Intelligent nanoflowers: a full tumor microenvironment-responsive multimodal cancer theranostic nanoplatform

Abstract: Multistage pH/H2O2/redox-responsive 3D nanoflowers that fully exploit the tumor microenvironment achieve highly specific guided multimode diagnosis with excellent synergistic chemotherapy and photodynamic therapy effects both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…It is noteworthy that the light irradiation power density (50 mW/cm 2 ) and irradiation dose (≤5.25 J/cm 2 ) in this study are a lot lower than those used on other oxygen-generating Ce6 nanoparticles, which relied on MnO 2 (150 mW/cm 2 , 90 J/cm 2 [ 72 ] or 100 mW/cm 2 , 30 J/cm 2 [ 56 ]) or H 2 O 2 (750 mW/cm 2 , 45 J/cm 2 [ 73 ]) decomposition to produce O 2 . This supports the applicability of our PFPE-based nanoformulation (i.e., Ce6-P/W NE) in delivering a large amount of O 2 to the hypoxic tumor site, consequently improving PDT efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the light irradiation power density (50 mW/cm 2 ) and irradiation dose (≤5.25 J/cm 2 ) in this study are a lot lower than those used on other oxygen-generating Ce6 nanoparticles, which relied on MnO 2 (150 mW/cm 2 , 90 J/cm 2 [ 72 ] or 100 mW/cm 2 , 30 J/cm 2 [ 56 ]) or H 2 O 2 (750 mW/cm 2 , 45 J/cm 2 [ 73 ]) decomposition to produce O 2 . This supports the applicability of our PFPE-based nanoformulation (i.e., Ce6-P/W NE) in delivering a large amount of O 2 to the hypoxic tumor site, consequently improving PDT efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…They further checked the effect of magnetic targeting on MRI and showed that tumor targeting and retention of the NPs was further increased under the influence of magnetic field, resulting in the appearance of much enhanced signal intensity in T2-weighted MR images within the tumor. Jing et al (2019) constructed nanoflower composites of Fe 3 O 4 NPs core with MnO 2 nanoshell for CT imaging in vitro in HeLa cells. Besides, the nanocomposites containing Mn 2+ and Fe 3 O 4 also exhibited in vivo T2/T1-weighted MRI response and a characteristic concentration dependent darkening and brightening effect of negative T2 and positive T1-MR contrast agent.…”
Section: Cancer Theranostics Application Of Immunomodulatory Nanopartmentioning
confidence: 99%
“…showed that an intelligent nanoflower composite (FHCPC@MnO 2 ) could exploit the low pH and high levels of H 2 O 2 and GSH that exist in the TME ( Figure a). [ 85,86 ] IONP nanoclusters were encapsulated with a GSH and a pH‐responsive polyphosphazene (PPZ)‐drug conjugate layer and was then coated with a MnO 2 shell. In a slightly acidic, H 2 O 2 and GSH‐rich environment, the MnO 2 and PPZ layers were degraded.…”
Section: Internal Targets For Nanomaterials Activationmentioning
confidence: 99%
“…Reproduced with permission. [ 86 ] Copyright 2019, The Royal Society of Chemistry. A hybrid protein@inorganic nanodumpling (ND) system was designed to be activated by thiols, such as GSH, and low pH.…”
Section: Internal Targets For Nanomaterials Activationmentioning
confidence: 99%